Gorer Tower and the Biblical Edom Road - Cohen-Sasson, Eli (Palestine exploration quarterly, 2021)
The existence of an ancient road linking Edom and Judea, the Edom Road (Derech Edom), is documented in the biblical text. To date the most comprehensive research on the Edom Road was carried out by B. Rothenberg and Y. Aharoni, who suggested its likely route based on archaeological sites dating to Iron Age II in the Southern Judean Desert, along the northern bank of Nahal Heimar. In this article we will examine a site near Nahal Gorer, and analyse its spatial context in order to learn about the road network in the southern Judean Desert during the Iron Age II period.